PHYSICAL-MECHANICAL WOOD PROPERTIES FROM INVASIVE EXOTIC SPECIES OF ATLANTIC FOREST - Xavier, Carolina Nogueira; Ferreira, Raphaelly de Oliveira; Silva, Pedro Henrique de Paula; Silva, José Reinaldo Moreira da; Vanini, Andrea; Carvalho, Alexandre Monteiro de (Floresta, 2023)
Invasive exotic tree species cause several problems to the world biota. Removing these trees is important for restoring ecosystem balance. However, after the removal, there is a concern regarding the proper destination of the generated materials. The lack of knowledge about the wood characteristics makes it difficult to recommend for the most appropriate uses, which leads to a low added value of the product. The aim of the study was to assess the physical and mechanical wood properties and indicate the alternatives for using wood from exotic invasive species at the Fiocruz Mata Atlântica Biological Station, Rio de Janeiro - RJ. The three species studied were Artocarpus heterophyllus Lamarck (Jackfruit), Syzygium cumini (L.) Skeels (Java plum) and Clitoria fairchildiana R.A. Howard (Sombreiro). The physical and mechanical wood properties were determined in three distinct regions, denominated central, intermediate and external, ranging from pith-bark direction. The wood of Artocarpus heterophyllus had low basic density, retractions were lower in the central region, and the intermediate region had the highest mechanical resistance. The Syzygium cumini wood had medium density, the mechanical properties increased in the pith-bark direction, and the radial and volumetric retractions were lower in the central region. Clitoria fairchildiana wood had medium density and had the lowest mechanical resistance from the species evaluated. The three species have appropriate physical properties for the furniture sector, and the Syzygium cumini wood presented adequate mechanical resistance for civil construction.